2019
DOI: 10.3390/toxins11050258
|View full text |Cite
|
Sign up to set email alerts
|

NMR-Based Metabolic Profiles of Intact Zebrafish Embryos Exposed to Aflatoxin B1 Recapitulates Hepatotoxicity and Supports Possible Neurotoxicity

Abstract: Aflatoxin B1 (AFB1) is a widespread contaminant of grains and other agricultural crops and is globally associated with both acute toxicity and carcinogenicity. In the present study, we utilized nuclear magnetic resonance (NMR), and specifically high-resolution magic angle spin (HRMAS) NMR, coupled to the zebrafish (Danio rerio) embryo toxicological model, to characterize metabolic profiles associated with exposure to AFB1. Exposure to AFB1 was associated with dose-dependent acute toxicity (i.e., lethality) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 52 publications
5
50
0
3
Order By: Relevance
“…AFB1 acts as a type of human chemical toxicant, and the toxic effects of this toxicant are characterized by organophilism (mainly causing hepatic damage), genic toxicity (mainly inducing DNA damages such as hotspot mutation at codon 249 of TP53 gene, AFB1-DNA adduct formation, and so on), and carcinogenicity (mainly resulting in HCC) [6][7][8]. Among the hepatic toxicity of AFB1, the formation of AFB1-DNA adducts in hepatic cells is a key step during the metabolism of this toxicant [9][10][11][12][13][14]. Evidence from molecular epidemiological studies and clinical studies has proved that the levels of AFB1-DNA adducts in the hepatic tissues are positively associated with the levels and time of AFB1 exposure [3,24,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AFB1 acts as a type of human chemical toxicant, and the toxic effects of this toxicant are characterized by organophilism (mainly causing hepatic damage), genic toxicity (mainly inducing DNA damages such as hotspot mutation at codon 249 of TP53 gene, AFB1-DNA adduct formation, and so on), and carcinogenicity (mainly resulting in HCC) [6][7][8]. Among the hepatic toxicity of AFB1, the formation of AFB1-DNA adducts in hepatic cells is a key step during the metabolism of this toxicant [9][10][11][12][13][14]. Evidence from molecular epidemiological studies and clinical studies has proved that the levels of AFB1-DNA adducts in the hepatic tissues are positively associated with the levels and time of AFB1 exposure [3,24,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…AFB1-induced hepatic effects consist of acute toxic damages (such as severe DNA damage, severe liver degeneration and necrosis, and the failure of hepatic function) and chronic cumulative damages (such as a series of cumulative DNA damage, slight hepatocellular degeneration and necrosis, chronic inflammation, liver cirrhosis, and liver cancer) [3][4][5]. Increasing evidence has shown that under the same exposure of AFB1, some individuals feature severe hepatic damage; others have no noticeable damage [9][10][11][12][13][14]. This suggests that different individuals have different responses to the toxic effects of AFB1 and genetic factors may play a central role in the AFB1-induced hepatic toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…AFB1 is transferred into AFB1-DNA adducts and displays its genic toxicity and hepato carcinogenicity [3,19]. Mechanically, PHCC induced by AFB1 is mainly concerned with DNA damage (including DNA single-/double-strand breaks, base damage, adduct formation, genic mutation), the dysregulation of DNA repair, the activation of cancer genes (such as ras and myc), the inactivation of cancer suppressor genes (such as TP53, BP1, H2AX, bcl2, p21, and p27), inheritance alterations, and/or abnormal immunoreaction [1,[20][21][22][23][24][25]. Among these knowledge mechanisms and pathways, AFB1-DNA adducts and mutations at codon 249 of TP53 gene (also termed as hot-spot mutation induced by AFB1) have been especially concerned in the past decades [26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…In-cell NMR serves as a promising approach to provide structural and dynamics data on protein-protein interaction and protein-ligand interaction systems in cellular environments [ 45 , 49 , 151 ]. Generally, in-cell NMR can be carried out in bacteria, yeast, sf9, frog oocytes, zebrafish embryo, and human cells without further sample purification, and it has become a remarkable tool for drug discovery [ 45 , 152 , 153 , 154 , 155 , 156 , 157 , 158 ]. Multiple cases related to the applications of in-cell NMR in drug discovery have been reported.…”
Section: In-cell Nmrmentioning
confidence: 99%